The Institutional of Local Community and Stratification of Land Ownership in Surrounding Community Forests in Bogor - Tatan Sukwika; Dewi Nurhayati Yusuf; Ichsan Suwandhi (Institut Pertanian Bogor (IPB University), 2020)
Management of forest resources cannot be separated from the character attributes of the community. In the arena of community forest action, access to forest resources, which is a people's livelihood, is an important element. The study aimed to analyze the performance of the local community attributes towards community welfare and examine the stratification of community land ownership. This research was carried out in the qualitative descriptive analysis. The results of the analysis showed that 41.56% of the community forest farming groups classified as land-owners. Based on the strata of land ownership showed that 70% in the third strata, which was land-ownership of less than 0.5 ha. This study concluded that the institutional of local community was relatively low because not effective in regulating community behavior. These indicated by the low performance achieved on the welfare of the community, the low ownership of the area of arable land, and the level of welfare of the local community falls into the category of poor and low community education.